AKUNTABILITAS PEGAWAI DALAM PENGGUNAAN APLIKASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTERGRASI (SRIKANDI) PADA BADAN PENGAWAS PEMILIHAN UMUM PROVINSI BALI - Surya Widayani Ni Komang; Lilik Antarini; I Wayan Sudemen (Journal of Contemporary Public Administration, 2025)
The Bali Provincial Election Supervisory Body has started implementing an integrated dynamic archiving information system application since October 2023. Based on direct observation at the Bali Provincial Election Supervisory Body (BAWASLU) on December 16-19, 2024, there was a problem of employee accountability in using the SRIKANDI Application. There are three main problems: First, the lack of accountability related to understanding the use of the application, as seen from the lack of employee knowledge. Second, there is no direct accountability from Bali Provincial BAWASLU employees in dealing with hacker attacks that cause the SRIKANDI Application to be inaccessible. Third, there is no accountability related to the limitations of the application features, especially the absence of a notification feature for incoming mail. These problems underlie the importance of conducting research to determine employee accountability in using the SRIKANDI Application at the Bali Provincial Election Supervisory Body. The study uses the Accountability theory according to Sheila Elwood, namely, Legal and Honesty Accountability, Process Accountability, Program Accountability, and Policy Accountability. The research method uses qualitative descriptive. Data collection techniques through observation, interviews and documentation. The data sources for this study are primary data and secondary data. The study unit and informants of this research consisted of 4 informants consisting of 2 employees, the head of the section, and the head of the secretariat of the Bali Province Bawaslu. The data analysis technique used was through data condensation, data presentation, drawing and verifying conclusions. The results of the research on the accountability of Bali Province BAWASLU employees in using the SRIKANDI Application showed varying results in five aspects. Legal accountability is good with a strong regulatory basis. Honesty accountability is seen through monitoring that identifies deficiencies in user features. In process accountability, although the application increases efficiency, there are still security constraints due to hacker attacks. Program accountability is implemented in stages with tiered reports and is measured through the success of letter verification and TTE implementation. Policy accountability is characterized by a structured accountability system from the provincial to central levels that shows a commitment to smooth operations.